2007
DOI: 10.1063/1.2786588
|View full text |Cite
|
Sign up to set email alerts
|

Reliability properties of metal-oxide-semiconductor capacitors using HfO2 high-κ dielectric

Abstract: Articles you may be interested inHigh quality HfO2/p-GaSb(001) metal-oxide-semiconductor capacitors with 0.8nm equivalent oxide thickness Appl. Phys. Lett. 105, 222103 (2014); 10.1063/1.4903068Band offsets of metal-oxide-semiconductor capacitor with HfLaTaO/HfSiO stacked high-k dielectric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Recently, transition metal oxides such as tantalum oxide, titanium dioxide, aluminium oxide, zirconium oxide, hafnium oxide, lanthanum oxide and associated aluminates have emerged as alternative to SiO 2 gate dielectric material . Among those oxides, titanium dioxide (TiO 2 ) has great potential because of its high dielectric constant, high thermal stability and low leakage current density .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transition metal oxides such as tantalum oxide, titanium dioxide, aluminium oxide, zirconium oxide, hafnium oxide, lanthanum oxide and associated aluminates have emerged as alternative to SiO 2 gate dielectric material . Among those oxides, titanium dioxide (TiO 2 ) has great potential because of its high dielectric constant, high thermal stability and low leakage current density .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the reliability characteristics can be improved as the thickness of HfO 2 thickness decreases. 3 In terms of the current density fluctuations in Fig. 7 and the reliability characteristics in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Meanwhile, to maintain the physical thickness of gate oxide, HfO 2 has been considered as one of the most promising high-k materials to replace the conventional SiO 2 due to its high dielectric constant and good thermodynamics stability. [3][4][5] On the other hand, in order to test the ultrathin dielectric characteristics for MOS or non-volatile memory devices, large-area MOS capacitors (MOSCAPs) are still commonly used. The capacitance-voltage (C-V) measurement is an important technique to investigate the electrical characteristics of MOS devices.…”
mentioning
confidence: 99%
“…Every cell is associated with a defect generation rate (k) and some of the columns are represented as grain boundaries (GB) with a higher value of k that arises due to higher local relative permittivity at GB locations due to increased oxygen deficiency [15]. We simulate the forming process for t ox -$ 2.4 nm, 3.6 nm and 4.8 nm, considering a defect size of a 0 $ 8 Å [16]. The standard Monte Carlo procedure is implemented where the next location of defect evolution is chosen based on a random number generator, considering the weightage of the k values at the grain and GB locations.…”
Section: Methodology Of Forming Simulationmentioning
confidence: 99%